Kebijakan Pemerintah Menambah Kadar Crude Palm Oil (CPO) dalam BBM Biosolar sebagai Upaya untuk Memberikan Dampak Positif Regional bagi Perekonomian Indonesia - M. Usman Abdullah Tarigan; Zultri Aulia Siregar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In making BioSolar fuel, the government uses a hybrid concept, partly using petroleum and mixed with vegetable materials. In this research, the author would like to convey that this government activity can also use more local materials, because as we know, Indonesia is a CPO producing country. is the largest in the world, therefore through this activity the government can make better use of Indonesia's resources, for a better Indonesia. This research uses a qualitative research method with a descriptive approach where researchers observe a phenomenon of increasing levels of palm oil (CPO) in diesel fuel currently, namely from B30 to B35.